Identifying Structural Damage in Steel Truss Frames Using Computer-Based Numerical Simulation with the Second Order Blind Identification (SOBI) Method - Haurissa, Ryan (Rekayasa Sipil, 2024)
The failure of the building work is due to the structure failing to function and can also cause material losses and can even cause fatalities. Because of that, excellent and careful anticipation is needed. In this regard, the re-search that will be carried out is monitoring the structure's health by identifying structural damage based on vi-bration tests. Modal structural parameters are determined based on the vibration output using the Second Order Blind Identification algorithm created by numerical simulation in the MATLAB application. The method in this research is a laboratory experiment with two testing models, namely the modal parameter values of the typical truss structure and the damaged truss structure, using the Second Order Blind Identification algorithm method. Furthermore, analyzing the indications of structural damage from the estimated modal parameters, the accuser, and the effectiveness of the Second Order Blind Identification algorithm method is feasible to use. The results showed that the Hp sensor recording data that had been processed were the health15mts.mat and dam-age15mts.mat files loaded into the SOBI program, and the predicted value of the natural frequency of typical structures was 31,9072  rad/s, and damaged structures were 22,6089 rad/s. From the expected frequency, the frequency ratio value is 41.127 %. According to the Steel Frame Bridge Inspection Regulation No.005/BM/2009 Guidelines for Construction and Building of the Ministry of Public Works, Directorate General of Highways, if it exceeds 20%, it can be categorized as critical.